Attendance Information System Utilizing Global Positioning System (GPS) Using Appsheet Application: Sistem Informasi Daftar Hadir Memanfaatkan Global Positioning System (GPS) Menggunakan Aplikasi Appsheet - Habibah, Endah Ummu; Sumarno, Sumarno (Universitas Muhammadiyah Sidoarjo, 2022)
In the current developing era, there are many ways to detect the presence of a person in an agency or company. Starting from the type of presence using fingerprints, the person's face and location, and the identification card at the institution the person works at. Many attendance lists use fingerprints but have shortcomings in the form of inaccuracies in the fingerprint application. Therefore, we conducted a study, designed and implemented an application to detect a person's presence using location using the Global Positioning System (GPS) method. This study aims to provide accuracy in carrying out a person's attendance list so that there will be no cheating by where someone does attendance according to that person's presence. In this study, in addition to using location as a basis for taking attendance, it is also equipped with the date, time, location, and real-time photos of yourself. The results obtained from this application are in the form of a person's attendance report that is accurate both from time and location as well as someone who does the attendance.